50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Adams, Michael J.; Lefkowitz, Elliot J.; King, Andrew M. Q.; Harrach, Balázs; Harrison, Robert L.; Knowles, Nick J.; Kropinski, Andrew M.; Krupovic, Mart; Kuhn, Jens H.; Mushegian, Arcady R.; Nibert, Max L.; Sabanadzovic, Sead; et al. (Archives of virology, 2017)
We mark the 50th anniversary of the International Committee on Taxonomy of Viruses (ICTV) by presenting a brief history of the organization since its foundation, showing how it has adapted to advancements in our knowledge of virus diversity and the methods used to characterize it. We also outline recent developments, supported by a grant from the Wellcome Trust (UK), that are facilitating substantial changes in the operations of the ICTV and promoting dialogue with the virology community. These developments will generate improved online resources, including a freely available and regularly updated ICTV Virus Taxonomy Report. They also include a series of meetings between the ICTV and the broader community focused on some of the major challenges facing virus taxonomy, with the outcomes helping to inform the future policy and practice of the ICTV.